Achieving UHC in Samoa through Revitalizing PHC and Reinvigorating the Role of Village Women Groups - Rasul Baghirov; John Ah-Ching; Caroline Bollars (Taylor & Francis Group, 2019)
The increasing prevalence of NCDs such as cardio-vascular diseases, diabetes and kidney failure represents a threat to sustainable development in Samoa. The aim of this commentary is to describe the important role played by women in the community in relation to public health and to detail the lessons learnt and results of a community-based NCD prevention and management package that utilizes the strengths of community engagement at primary care level to accelerate progress towards UHC. The impetus of reforms in Samoa is to strengthen community-based care and rebuild its foundation-Primary Health Care (PHC). In doing so, the government is reinvigorating the role of women's village committees in identifying and referring people with high risks factors for non-communicable diseases. In 2015, an attempt to reinvigorate the role of Komiti Tumama in health was undertaken to address the high burden of non-communicable diseases. The government together with WHO launched a demonstration project, "NCD early detection and self-management through community participation (PEN Fa'a Samoa)", which aimed to address key issues on NCDs through an approach of contextualizing universal health coverage. Preliminary results of the program implementation are positive. PEN Fa'a Samoa achieved a high level of population screening coverage in the demonstration villages, in which the women's committee representatives played a key role. Samoa has shown in this example how such action can strengthen its health system, by utilizing critical human resources at a community level, which have proven to be essential to support the functioning of health services.